The Influence of Sharia Compliance and Profitability on Islamic Social Reporting Disclosure - Adzima, Sisda; Rahmah, Nunung (Universitas Bangka Belitung, 2026)
The significant growth and expansion of the Islamic capital market has created an urgent need for corporations to balance financial performance with spiritual accountability and transparency with Islamic Social Reporting Disclosure. This study aims to examine the effect of sharia compliance and profitability on Islamic Social Reporting Disclosure in companies included in the Jakarta Islamic Index for the 2020–2024 period. This study utilizes a quantitative methodology using, secondary data from annual reports of firms listed on the Indonesia Stock Exchange for the 2020–2024 period. Through purposive sampling, 16 representative firms were selected and the analysis was conducted using panel data regression with EViews 13. Empirical evidence suggests that while Sharia compliance does not significantly drive Islamic Social Reporting Disclosure. In contrast, profitability exerts a positive and significant influence. However, both independent factors are present simultaneously, significantly affecting.